2019
DOI: 10.1186/s12935-019-0733-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 2D and 3D cell cultures on treatment response, EMT profile and stem cell features in head and neck cancer

Abstract: BackgroundHead and Neck Squamous Cell Carcinoma (HNSCC) tumors are often resistant to therapies. Therefore searching for predictive markers and new targets for treatment in clinically relevant in vitro tumor models is essential. Five HNSCC-derived cell lines were used to assess the effect of 3D culturing compared to 2D monolayers in terms of cell proliferation, response to anti-cancer therapy as well as expression of EMT and CSC genes.MethodsThe viability and proliferation capacity of HNSCC cells as well as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
148
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(182 citation statements)
references
References 29 publications
15
148
1
Order By: Relevance
“…Further examination of 2D cultures suggests different patterns of gene expression emerge compared to in vivo and 3D culture experiments. In a study examining head and neck cancer cell lines, cancer stem cell (CSC) genes (NANOG and SOX2) were down regulated in 2D culture compared to 3D models [20]. Similar results were found in bladder cancer with T24 cell spheres expressing higher levels of mRNA and protein levels of NANOG compared to 2D culture [21].…”
Section: Two-dimensional Tissue Culturementioning
confidence: 59%
“…Further examination of 2D cultures suggests different patterns of gene expression emerge compared to in vivo and 3D culture experiments. In a study examining head and neck cancer cell lines, cancer stem cell (CSC) genes (NANOG and SOX2) were down regulated in 2D culture compared to 3D models [20]. Similar results were found in bladder cancer with T24 cell spheres expressing higher levels of mRNA and protein levels of NANOG compared to 2D culture [21].…”
Section: Two-dimensional Tissue Culturementioning
confidence: 59%
“…Tumor cells are known to be more resistant to drugs in 3D than in 2D cultures due to reduced access to compounds and pathophysiological differences such as hypoxia, which leads to activation of cell survival genes [29]. However, some studies showed that cells can also be more sensitive in 3D cultures compared to 2D cultures [30,31]. Melissaridou et al showed head and neck squamous cell carcinoma cell line LK0902 was more sensitive to cetuximab, which is an epidermal growth factor receptor (EGFR) inhibitor in 3D conditions compared to 2D [30].…”
Section: Discussionmentioning
confidence: 99%
“…The schematic representation of the in vitro experimental workflow used for determining the MDR profile is provided below (Scheme 1). The cell lines LK0912, LK0917, and LK1108 used in our experiments, were established from three different HNSCC patients as reported previously by our team 25,26 . As reported previously 25,26 , biopsies were excised from the tumors of gingiva, tongue, and hypopharynx and harvested immediately for establishing monolayer cell lines in vitro.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, owing to their multicellular nature, MCSs spontaneously develop MDR against many chemotherapeutic drugs 23,24 , thus making them the appropriate model system for the purpose of the present study. Recently, members of our group reported a marked treatment response difference between 2D cell cultures and MCSs of head and neck cancer cells pertaining to epithelial-mesenchymal transition and stem cell characteristics, suggesting that 3D cell cultures are clinically relevant models that are superior to 2D monolayers for the investigation of new therapeutic targets 25 . However, there is no well-defined in vitro method or criteria for the identification of the resistance status of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation